(untitled) (Iraqi Journal of Medical Sciences, 2022)
Background: A corona virus (COVID-19) pandemic in Iraq has extended all over the country, including Fallujah city in western of Iraq. Being aware of the epidemiological features of this novel disease can greatly assist in making the suitable decisions regarding the management and thus control of this epidemic. Objective: To study the epidemiological characteristics of COVID-19 patients in Fallujah city, Iraq. Methods:In this retrospective study, information in regard to the epidemiological features of COVID-19 suspected cases who underwent polymerase chain reaction (PCR) testing at Fallujah Teaching Hospital in Fallujah, Al-Anbar, Iraq, from September 12th, 2020 to January 5th, 2021. Inclusive, have been collected, analyzed and then reported. General features including age, sex, occupation and quarantine site were investigated. Whole data were retrieved from patients’ official records. Results: A total 3604 samples from COVID-19 suspected cases were collected, 575 cases of them were tested positive for COVID-19. Among the COVID-19 patients, 402 of them were males (69.9%) and 173 were females (30.1%). The age range of the patients was (15-86) years and the mean age ±SD was 40.98±14.3 years. Forty-one COVID-19 patients were healthcare workers (7.1%) and the rest 534 patients had non-healthcare related occupations (92.9%). Only 40 COVID-19 positive cases were admitted to the hospital (7%), and 535 patients were in home quarantine (93%). In case of the total 143 hospital admitted patients, the PCR test results were negative in 103 patients (72%) and positive in only 40 patients (28%). Conclusion: This study found that COVID-19 was more prevalent among the young male individuals, whom represent the community active group. This study can serve in documenting the features of the patients with COVID-19 in Fallujah, Iraq, and also in helping the healthcare workers in detecting and managing the patients. Keywords: COVID-19, Coronavirus, epidemiology, SARS-CoV-2, Iraq Citation: Taher NM, Abady NH, Jamal QW. A retrospective study regarding coronavirus disease epidemiological features among people in Fallujah City, Iraq. Iraqi JMS. 2022; 20(2): 201-206. doi: 10.22578/IJMS.20.2.6